Scaling of Yu-Shiba-Rusinov energies in the weak-coupling Kondo regime. Issue 1 (December 2017) - Hatter, Nino; Heinrich, Benjamin; Rolf, Daniela; Franke, Katharina
Abstract The competition of the free-spin state of a paramagnetic impurity on a superconductor with its screened counterpart is characterized by the energy scale of Kondo screening compared to the superconducting pairing energy Δ. When the experimental temperature suppresses Kondo screening, but preserves superconductivity, i.e., when Δ/k B  > T  > T K (k B is Boltzmann's constant andT K the Kondo temperature), this description fails. Here, we explore this temperature range in a set of manganese phthalocyanine molecules decorated with ammonia on Pb(111). We show that these molecules suffice the required energy conditions by exhibiting weak-coupling Kondo resonances. We correlate the Yu-Shiba-Rusinov bound states energy inside the superconducting gap with the intensity of the Kondo resonance. The observed correlation follows the expectations for a classical spin on a superconductor. This finding is important in view of many theoretical predictions using a classical spin model, in particular for the description of Majorana bound states in magnetic nanostructures on superconducting substrates. The description of a paramagnetic impurity on a superconductor remains elusive in the weak-coupling Kondo regime. Here, Hatter et al. correlate the energy of the Yu-Shiba-Rusinov bound states with the intensity of the Kondo resonances in such a regime, revealing a behavior well described by classical spin models.